Variations on variations: from Miklós Erdély to artificial intelligence - Pál, Gyöngyi (ARTCADIA, 2023)
The article explores the phenomenon of “variation” throught the paradox of the divisibility of one. If the one is divisible, then we claim that the “one” is also many, i.e. it is the opposite of itself. Variations retain their identity with the original while their difference becomes important. Miklós Erdély’s investigations and theses provide a good basis for examining this paradox. Although Erdély starts from the notions of identity and repeatability, he also incorporates seemingly contradictory variations based on modification of the iteration. As with biological mutation, randomly generated variations based on repetition play an important role in computer-generated art. Variations are an essential element of Net-Art and AI-generated artworks, and this article explores their characteristics.
Keywords: Net-art; Miklós Erdély; AI-art; iteration; variation